MicroRNA 3′ ends shorten during adolescent brain maturation - Thomas, Kristen T.; Vermare, Anaïs; Egleston, Suzannah O.; Wang, Yong-Dong; Mishra, Ashutosh; Lin, Tong; Peng, Junmin; Zakharenko, Stanislav S. (Frontiers in Molecular Neuroscience, 2023)
MicroRNA (miRNA) dysregulation is well-documented in psychiatric disease, but miRNA dynamics remain poorly understood during adolescent and early adult brain maturation, when symptoms often first appear. Here, we use RNA sequencing to examine miRNAs and their mRNA targets in cortex and hippocampus from early-, mid-, and late-adolescent and adult mice. Furthermore, we use quantitative proteomics by tandem mass tag mass spectrometry (TMT-MS) to examine protein dynamics in cortex from the same subjects. We found that ~25% of miRNAs’ 3′ ends shorten with age due to increased 3′ trimming and decreased U tailing. Particularly, shorter but functionally competent isoforms (isomiRs) of miR-338-3p increase up to 10-fold during adolescence and only in brain. MiRNAs that undergo 3′ shortening exhibit stronger negative correlations with targets that decrease with age and stronger positive correlations with targets that increase with age, than miRNAs with stable 3′ ends. Increased 3′ shortening with age was also observed in available mouse and human miRNA-seq data sets, and stronger correlations between miRNAs that undergo shortening and their mRNA targets were observed in two of the three available data sets. We conclude that age-associated miRNA 3′ shortening is a well-conserved feature of postnatal brain maturation.